Low vitamin D exposure and risk of nasopharyngeal carcinoma: Observational and genetic evidence from a multicenter case–control study. Issue 9 (September 2021) - Mai, Zhi-Ming; Ngan, Roger Kai-Cheong; Ng, Wai-Tong; Lin, Jia-Huang; Kwong, Dora Lai-Wan; Yuen, Kam-Tong; Lee, Cheuk Kwong; Leung, Jennifer Ngar-Sze; Ip, Dennis Kai-Ming; Chan, Yap-Hang; Lee, Anne Wing-Mui; Lung, Maria Li; et al.
Summary: Background & aims: Little is known about the risk of nasopharyngeal carcinoma (NPC) in relation to vitamin D exposure. The aim of this study was to examine the associations of NPC risk with serum level of 25-hydroxyvitamin D (25OHD) and genetic predicted 25OHD, and potential effect modification by several putative risk factors of NPC. Methods: Our multicenter case–control study in Hong Kong recruited 815 NPC cases and 1502 frequency-matched (by sex and age) hospital controls from five major regional hospitals, and recruited 299 healthy subjects from blood donation centers (2014–2017). Circulating level of 25-hydroxyvitamin D (25OHD) and genetic predicted 25OHD (rs12785878, rs11234027, rs12794714, rs4588 and rs6013897) were measured by validated enzyme immunoassay and the iPLEX assay on the MassARRAY System, respectively. Data were also collected on demographics, lifestyle factors, ultraviolet radiation exposure, and potential confounders using a computer-assisted, self-administered questionnaire with satisfactory test-retest reliability. Unconditional logistic regression models were used to estimate ORs and 95% CIs. Results: Despite no significant association of NPC risk with circulating 25OHD and genetic predicted 25OHD, there was evidence for an inverse association in participants with normal body mass index (between 18.5 and 27.5) across categories of 25OHD ( P trend = 0.003), and a positive association in those with low socioeconomic status across categories based on the genetic score ( P trend = 0.005). In addition, risk of NPC diagnosed at an early stage was higher for genetically lower 25OHD level (adjusted OR = 3.09, 95% CI = 1.04–9.21, P trend = 0.022). Conclusions: Findings of this first comprehensive study to investigate the positive association of NPC risk with vitamin D deficiency need to be confirmed and be best interpreted with results of further similar studies. Our findings may inform possible etiological mechanisms of the associations with several putative risk/protective factors of NPC.